2019
DOI: 10.1021/acs.jpclett.9b02581
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Coherent Emission from Ionized Nitrogen Molecules by Femtosecond Laser Pulses

Abstract: The forward emission spectra were experimentally measured for ionized nitrogen molecules by an 800 nm pump laser and a delayed seed laser. It was found that emission lines around both 428 and 391 nm are greatly enhanced upon use of a 391 or 428 nm seed laser. The emission lines around 391 and 428 nm can be assigned to the rotational transitions of N2 + [B2Σu +(v′ = 0) → X2Σg +(v = 0)] and N2 + [B2Σu +(v′ = 0) → X2Σg +(v = 1)], respectively. They originate from seed-induced superfluorescence and resonant stimul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 30 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Nevertheless, it would be of great importance to explore alternative solutions involving more abundant elements and molecules which are also less chemically reactant and safe to use. In particular, molecular nitrogen ions (N ), which can easily be produced from atmospheric nitrogen using high-intensity femtosecond pulses, emerge as the intriguing model system for exploring quantum coherence effects from abundant energy levels that exhibit rich electron and molecular dynamics [26][27][28][29][30][31][32]. In such a system, the energy diagram is significantly different from that of an atom, i.e., energy differences between lower electronic states of molecular ions are located in near-ultraviolet, visible and near-infrared spectral regions, making it easy to efficiently manipulate the quantum coherence between multiple states by using commonly available lasers.…”
mentioning
confidence: 99%
“…Nevertheless, it would be of great importance to explore alternative solutions involving more abundant elements and molecules which are also less chemically reactant and safe to use. In particular, molecular nitrogen ions (N ), which can easily be produced from atmospheric nitrogen using high-intensity femtosecond pulses, emerge as the intriguing model system for exploring quantum coherence effects from abundant energy levels that exhibit rich electron and molecular dynamics [26][27][28][29][30][31][32]. In such a system, the energy diagram is significantly different from that of an atom, i.e., energy differences between lower electronic states of molecular ions are located in near-ultraviolet, visible and near-infrared spectral regions, making it easy to efficiently manipulate the quantum coherence between multiple states by using commonly available lasers.…”
mentioning
confidence: 99%
“…Since then, more and more novel filamentation-based phenomena have been reported, and filamentation-based applications have been proposed, even to control weather. , In recent years it was found that some coherent radiations in air filaments are emitted along or opposite to the laser propagation direction. The emissions around 391 and 428 nm have been assigned to the B 2 Σ u + ( v ′ = 0) → X 2 Σ g + ( v ″ = 0, 1) transition of N 2 + , where v ′ and v ″ are the vibrational quantum numbers of the upper and lower states, respectively. They are predominantly emitted in the forward direction, and their formation mechanism depends on the wavelength of the pump laser. The most interesting observation is the backward emission lines at 337 and 357 nm, which can be assigned to the C 3 Π u ( v ′ = 0) → B 3 Π g ( v ″ = 0, 1) transition of N 2 . This backward stimulated radiation has the advantage of bringing information on the target of interest in the sky toward the ground observer. It holds the potential to greatly improve the detection sensitivity of optical remote sensing in comparison with omnidirectional fluorescence.…”
mentioning
confidence: 99%
“…This kind of mirror-free coherent emission of ambient air has potential application in remote sensing and has attracted great interest. The generation of the coherent emission around 391 nm, corresponding to the transition of N + 2 (B 2 Σ + u , ν = 0 → X 2 Σ + g , ν = 0), has been extensively investigated [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. The underlying mechanism is much more complicated when the pump laser wavelength is around 800 nm [10].…”
mentioning
confidence: 99%